Distribution, provenance and early diagenesis of major and trace metals in sediment cores from the Mandovi estuary, western India. (5th March 2016) - Prajith, A.; Rao, V. Purnachandra; Chakraborty, P.
Abstract: Major elements and trace metals were analyzed in four sediment cores recovered along a transect in the Mandovi estuary for their distribution, provenance and early diagenesis. The sediments were clayey silts in cores from the upper/lower estuary and sand-dominated in cores from the middle estuary/bay. Organic carbon (OC) content varied from 0.5 to 4%, with higher values in fine-grained sediments. The mean Fe and Mn contents of sediments from the upper/middle estuary were 3–5 times and 8–13 times, respectively higher than the reference sediment (RS) from the same estuary. The mean Fe and Mn contents of sediments from the lower estuary/bay were close to the RS. Strong inter-metal correlation among Ti, V, Cr and Zr in all the cores indicated their contribution from a common source, probably the laterites from hinterland. Trace metals were more enriched in fine-grained sediments than in sand-dominated sediments. Early diagenetic control on the redistribution of metal is evident in core sediments from the middle estuary to Bay. The distribution of Mo, U and Pb followed that of Fe and Mn in the upper estuary and OC in the lower estuary/bay. Our results indicated strong anthropogenic contribution of metals from ore deposits in the upper/middle estuary. The Mn and Cr contents of sediment in the upper/middle estuary and Fe in the middle estuary were highly enriched suggestive of 'significant pollution signal'. More trace metals from the middle estuary were moderately enriched. Speciation studies showed Mn and Pb occurred abundantly in non-residual phases. High Mn content and its high percentage in exchangeable and reductive phases indicate that it was susceptible to be mobilized. However, Fe, Cu and Ni occurred abundantly in residual phases and less percentage of them were expected to be bio-available. Highlights: Major and trace metal distribution in 4 sediment cores from the Mandovi estuary. Contrasting metal contents in the upper/middle estuary and lower estuary/bay. Two distinct sources of sediments, ore deposits and laterites. Trace metal distribution controlled by grain size, OC and early diagenesis. High Mn and Pb in non-residual phase and, high Fe, Ni and Cu in residual phases.